“Coordinación automática de protecciones de sobre corriente en sistemas radiales elaborado en APP DESIGNER” - Pinos Ponce, Alex Patricio (2021)
This research project presents a technological proposal that seeks to coordinate utomatically over-current protections for radial systems. As results present starting current, instantaneous current (50), DIAL, time variation (DT), transformation ratio (TC), instantaneous timed and relay curve description. It tries to provide the user with a fast and accurate analysis for calibration of a radial system by means of a minimum operating time between the relays, which is the margin discrimination time for optimal coordination. The application was developed in the language MATLAB R2020b programming consisting of a built-in option, App Designer is an effective tool for programming code interfaces, which allowed to get the main platform of the proposal Automatic Coordination of Optimal Relays. CAR.OP performs data validation between all currently standardized curves, to select the minimum delay time between ones. Time that has to approach the margin discrimination set by the system. This application is focused on the Electric Engineering Career, through the validation of results with LSPS software and exercises proposed, it was demonstrated that the application has a minimum margin of error, was used as a guide the IEEE standard for inverse equations for over current relays" and the IEC "Measurement Relays and Protective Equipment" for automatic design in the coordination and analysis of protection. Which demonstrates the appropriate adjustment parameters for a system